2010
DOI: 10.1051/0004-6361/200913278
|View full text |Cite
|
Sign up to set email alerts
|

Circumstellar H I and CO around the carbon stars V1942 Sagittarii and V Coronae Borealis

Abstract: Context. The majority of stars that leave the main sequence are undergoing extensive mass loss, in particular during the asymptotic giant branch (AGB) phase of evolution. Observations show that the rate at which this phenomenon develops differs widely from source to source, so that the time-integrated mass loss as a function of the initial conditions (mass, metallicity, etc.) and of the stage of evolution is presently not well understood. Aims. We investigate the mass loss history of AGB stars by observing the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 31 publications
3
17
1
Order By: Relevance
“…H i line profiles obtained at different positions on and around the central star were well fitted by such a model with a gas temperature decreasing from 1800 K, in r 1 , to 170 K, in r f . Libert et al applied the same model to other sources, like RX Lep, an oxygen‐rich star (Libert et al 2008), and V1942 Sgr, another carbon star (Libert et al 2010a). In general, the gas detached shell model of Libert et al (2007) accounts well for the H i emission of evolved stars, which are characterized by a narrow‐line profile (∼2–4 km s −1 ) approximately centred on the stellar radial velocity (Gérard & Le Bertre 2006).…”
Section: Discussionmentioning
confidence: 97%
“…H i line profiles obtained at different positions on and around the central star were well fitted by such a model with a gas temperature decreasing from 1800 K, in r 1 , to 170 K, in r f . Libert et al applied the same model to other sources, like RX Lep, an oxygen‐rich star (Libert et al 2008), and V1942 Sgr, another carbon star (Libert et al 2010a). In general, the gas detached shell model of Libert et al (2007) accounts well for the H i emission of evolved stars, which are characterized by a narrow‐line profile (∼2–4 km s −1 ) approximately centred on the stellar radial velocity (Gérard & Le Bertre 2006).…”
Section: Discussionmentioning
confidence: 97%
“…Nuclear star clusters with young stellar populations, such as the one in our Galactic center, produce winds with high velocities up to 2000 km s −1 from Wolf-Rayet and other young stars (Cuadra et al 2008). However, old stellar populations mostly shed matter and produce winds from asymptotic giant branch (AGB) stars (Vassiliadis & Wood 1993;Hurley et al 2000;Groenewegen et al 2007) with a correspondent wind velocity under 50 km s −1 (Knapp et al 1982;Marengo 2009;Libert et al 2010;Leitner & Kravtsov 2011). We use the terms "stellar winds" and "mass lost by stars" interchangeably, while having in mind that AGB stars shed mass also via planetary nebulae.…”
Section: Energy Injectionmentioning
confidence: 96%
“…The proximity of ASAS 191909−1554.4 allows its circumstellar dust shell to be resolved in IRAS images (e.g., Young et al 1993), and Egan & Leung (1991) use ASAS 191909−1554 and other carbon stars with resolved dust shells and 100 µm excess to statistically argue that each of these stars must be surrounded by two dust shells, one that is old, ∼10 4 yr, and the other that is produced by a current episode of mass loss. Recent H I observations by Libert et al (2010) have shown evidence for the presence of H in the circumstellar shell of ASAS 191909−1554.4. The shallow, symmetric fade of the light curve, along with the N type carbon star spectrum and the presence of 13 C in the spectrum, leads us to conclude that ASAS 191909−1554.4 is a DYPer.…”
Section: Asas 170541−26501 (Gv Oph)mentioning
confidence: 98%